2022
DOI: 10.3390/v14081617
|View full text |Cite
|
Sign up to set email alerts
|

Detection of African Swine Fever Virus in Ornithodoros Tick Species Associated with Indigenous and Extralimital Warthog Populations in South Africa

Abstract: We investigated the possibility that sylvatic circulation of African swine fever virus (ASFV) in warthogs and Ornithodoros ticks had extended beyond the historically affected northern part of South Africa that was declared a controlled area in 1935 to prevent the spread of infection to the rest of the country. We recently reported finding antibody to the virus in extralimital warthogs in the south of the country, and now describe the detection of infected ticks outside the controlled area. A total of 5078 tick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…A study out of South Africa showed there were ASFV seropositive warthogs in an area thought to be free of disease and further investigation revealed that the Ornithodoros spp. were also infected with ASFV in that area ( 45 ). This suggests that the area was initially declared free based on the pig status but not based on the Ornithodoros spp.…”
Section: Discussionmentioning
confidence: 99%
“…A study out of South Africa showed there were ASFV seropositive warthogs in an area thought to be free of disease and further investigation revealed that the Ornithodoros spp. were also infected with ASFV in that area ( 45 ). This suggests that the area was initially declared free based on the pig status but not based on the Ornithodoros spp.…”
Section: Discussionmentioning
confidence: 99%
“…This dramatic shift in the epidemiology of ASF outbreaks in domestic pigs and recent evidence of ASF infection in warthogs in the Northern Cape Province [ 58 ] suggests that ASFV spill-over to the warthog population, with the probable establishment of the warthog-tick sylvatic cycle, has occurred in areas distant from the ASF controlled area. Molecular screening of ticks from warthog burrows at a large number of localities in South Africa revealed the presence of genotype Ia and Ic variants in ticks from warthog burrows, as well as a genotype III strain in warthog burrow ticks in the Free State province [ 59 ]. A possible explanation for this extralimital establishment of sylvatic cycle ASFV is that seronegative warthogs translocated to areas outside the controlled area [ 37 ] were infested with Ornithodoros nymphs, as has been reported previously [ 60 , 61 , 62 ].…”
Section: Geographical Distribution Of Ornithodoros ...mentioning
confidence: 99%
“…For more than half a century, outbreaks of ASF in domestic pigs in South Africa were restricted to an ASF-controlled area proclaimed in 1935 where the warthog–tick sylvatic cycle was endemic, with occasional spill over into the immediate environs of the area. However, extra-limital spread of warthogs has been widely reported, and the original study on Ornithodoros ticks from warthog burrows revealed ASD virus infection in ticks from several sites distant from the proclaimed endemic area [ 6 ].…”
mentioning
confidence: 99%